-6(3x-1)=-18x-6

Simple and best practice solution for -6(3x-1)=-18x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(3x-1)=-18x-6 equation:


Simplifying
-6(3x + -1) = -18x + -6

Reorder the terms:
-6(-1 + 3x) = -18x + -6
(-1 * -6 + 3x * -6) = -18x + -6
(6 + -18x) = -18x + -6

Reorder the terms:
6 + -18x = -6 + -18x

Add '18x' to each side of the equation.
6 + -18x + 18x = -6 + -18x + 18x

Combine like terms: -18x + 18x = 0
6 + 0 = -6 + -18x + 18x
6 = -6 + -18x + 18x

Combine like terms: -18x + 18x = 0
6 = -6 + 0
6 = -6

Solving
6 = -6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 12+4l=18-3l | | 4a^4+12a^3+16a= | | 2x+9=108 | | 5-(-f)=12 | | -6(3x-1)=-18-6 | | (4x-62)=90 | | 3(7x-6)=24 | | (x+4)=2(x-7) | | -2(3x+3)=-6x+6 | | a+5.7=-2.3 | | 12+3l=18-2l | | 4x-62=x | | 7c-5=6 | | 3x+39+5x+10=180 | | 30a^2-54a+24= | | 5k+10=10k-7 | | 4/100+1=2.2/10 | | 3x^2-15x=20 | | c=8p+25+4 | | (2x+4)=28 | | n+5=9*3 | | 4y+2=-.3(8-12y) | | (4x+60)=120 | | d-3=(13) | | x-(4x-7)=5x-x+21 | | 2x+9-6W=-19 | | -4.2+31.5=-65.1x | | -15000000x+3056890000=5550000x+2085000000 | | p-(23)=11 | | -8=2/x | | 36a-9= | | 10k=2 |

Equations solver categories